Gold Nanoparticles: Preparation, Properties, Functionalization and Application - Li Yutong (MATEC Web of Conferences)
Gold nanoparticles (AuNPs) are a type of nano-scale gold particles with diameters ranging from 1 to 100 nanometers. These nanoparticles have three main characteristics. First of all, they have a high electron density, which enables them to be clearly visible under an electron microscope. Secondly, it has a significant dielectric response and can strongly react to the applied electric field. Thirdly, they have highly efficient catalytic activity, which can promote specific chemical reactions. These characteristics enable them to selectively bind to biological macromolecules such as proteins and DNA, while fully maintaining the natural structure and functional activity of these molecules. Due to its unique size, shape, characteristics and wide range of potential applications, it plays an important role in science and tecnology. In recent years, the research of gold nanoparticles and its new application have been carried out inland and abroad. In addition, remarkable progress has been made concerning with the preparation, properties, functionalization and application of AuNPs. Therefore, this paper mainly studies the preparation and characteristics of gold nanoparticles and summarizes its applications in life.